Peran Kader Posyandu Dalam Mendukung Penanganan Angka Stunting Di Desa Sibalaya Barat - Fardi Fardi; Muh. Ali Murad; Harnida Wahyuni Adda (Manajemen Kreatif Jurnal, 2023)
The role of Posyandu cadres in supporting the handling of stunting rates is really needed, not only when Posyandu cadres should also make visits to toddlers’ homes by providing health education. Mothers also have to realize that Posyandu is also important in the growth and development of toddlers. This research examines the role of posyandu cadres in supporting the handling of stunting rates. Based on the results of the implementation of this community service program, it was found that the role of posyandu cadres was appreciated by the community, namely such as informing the implementation of the posyandu regularly but the cadres never provided general counseling about the importance of posyandu activities. Therefore, in order to achieve posyandu implementation, cadres should carry out all their duties properly, especially cadres must also frequently provide health education to the community, especially mothers and toddlers.